2015
DOI: 10.1161/strokeaha.115.009716
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Carotid Calcification on Cranial Computed Tomography

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Visual scores provide an overall good, quick and reproducible measure of iICA calcification burden[18] whereas quantitative or volumetric calcification measurement are time intensive but do provide a more accurate (volumetric) depiction of the calcium load/burden. [1] However, the previous qualitative scores were not designed to separate intimal and medial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Visual scores provide an overall good, quick and reproducible measure of iICA calcification burden[18] whereas quantitative or volumetric calcification measurement are time intensive but do provide a more accurate (volumetric) depiction of the calcium load/burden. [1] However, the previous qualitative scores were not designed to separate intimal and medial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the calcium load was graded with a qualitative score and it was measured in a specific intracranial location. However, a recent study showed that visual scores correlate highly with quantitative calcification measures [18]. …”
Section: Discussionmentioning
confidence: 99%
“…(10,11) The MWVS scale assigns a score reflecting the severity of calcification on each axial slice in which the ICA is visible, starting just distal to the petrous temporal bone and ending at the level of the terminal bifurcation. A score of 0 reflects no calcification; 1 reflects thin, discontinuous calcification; 2 reflects thin and continuous or thick and discontinuous calcification; and 3 reflects thick, continuous calcification (Figure 1).…”
Section: Methodsmentioning
confidence: 99%